Effect of music on spatial performance: a test of generality - Rideout, B E; Dougherty, S; Wernert, L (Perceptual and motor skills, 1998)
Previous attempts by various researchers to replicate the enhancement of spatial performance following 10 min. exposure to music have been inconsistent in their findings. In the present study 16 subjects showed reliable improvement on a paper-folding-and-cutting task after listening to Mozart's Sonata for Two Pianos in D major, as employed by others. The enhanced performance was also noted for 16 other subjects after listening to a contemporary selection having similar musical characteristics. In both cases the control procedure included 10 min. of listening to a progressive relaxation tape.